A multimodality approach to sinonasal undifferentiated carcinoma: a single institute experience. Issue 1 (12th December 2016) - Bhasker, S; Mallick, S; Benson, R; Bhanuprasad, V; Sharma, A; Thakar, A
Abstract: Background: Sinonasal undifferentiated carcinoma is a rare aggressive tumour arising from the Schneiderian epithelium lining the sinonasal tract. Although considered the cornerstone of therapy, surgical resection can only be performed in a limited number of patients. This report describes the experience of treating sinonasal undifferentiated carcinoma with a multimodality approach. Method: The treatment charts of sinonasal undifferentiated carcinoma patients treated at a tertiary care centre from 2004 to 2012 were retrospectively reviewed. Results: A total of 16 sinonasal undifferentiated carcinoma patients with a median age at diagnosis of 47.5 years (range 8–65 years) were included: 19 per cent had neck nodal metastasis at presentation. Four patients (25 per cent) underwent surgery: of these, two had post-operative radiotherapy, one had pre-operative radiotherapy and one had adjuvant chemotherapy alone. Six patients (38 per cent) received definitive radiotherapy: five had received neoadjuvant chemotherapy to reduce tumour size and help in radiotherapy planning, while four (25 per cent) received palliative radiotherapy. The median follow up was 10.4 months (range 1–42.5 months). The estimated median progression-free survival time was 29.3 months. One- and three-year progression-free survival rates were 77 per cent and 41 per cent, respectively. Conclusion: Surgery is the best treatment option for sinonasal undifferentiated carcinoma, although most patients require post-operative radiotherapy for advanced disease and close tumour margins. Definitive radiotherapy with or without chemotherapy may be suitable for patients with inoperable locally advanced disease. Elective nodal irradiation to address the high nodal involvement rates should be considered to improve the survival rate.